Suitability of pristine carbon nanotube yarn tool for material removal by electrical discharges - YAYLA, PAŞA (My University, 2022)
High-intensity electrical discharges are used in the unconventional technique known as electrical discharge machining (EDM) to machine metals of any hardness. Due to their extraordinary conductivity and strength, carbon nanotubes (CNTs) have recently been explored in EDM too. However, material removal with CNT yarn (CNTY) has not been studied thoroughly. This work advocates the use of a pristine CNTY as an EDM tool. The feasibility is examined through characterization and material removal experiments. The measurements show that the CNTY ( 100 mu m) multi-ply tools extend tool life and, therefore, machining time by more than 14 s in the air and nearly 2.5 s in the oil. Other factors that restrict machining include intensified discharges and the shielding effect of the carbide layer formed on the workpiece.
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; MALZEME BİLİMİ, ÇOKDİSİPLİNLİ; Malzeme Bilimi; Mühendislik, Bilişim ve Teknoloji (ENG); MATERIALS SCIENCE, MULTIDISCIPLINARY; MATERIALS SCIENCE; Engineering, Computing & Technology (ENG); Metaller ve Alaşımlar; Malzeme Kimyası; Genel Malzeme Bilimi; Fizik Bilimleri; Metals and Alloys; Materials Chemistry; General Materials Science; Physical Sciences; CNT; carbon nanotube; CNT yarn; EDM; electrical discharge machining; material removal; FIBERS; SPUN; CONDUCTIVITY